PENINGKATAN KETERAMPILAN MENULIS SISWA KELAS IV SD MELALUI MODEL PROJECT BASED LEARNING BERBASIS BUKU CERITA KOMPARATIF - Rika Puspita; Anna Mariyani; Husna Imro'athush Sholihah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Writing skills of elementary students are still low due to limited idea development and weak use of language rules. This study aims to improve writing skills through Project Based Learning (PjBL) using a comparative storybook product. The research used classroom action research with two cycles. The subjects were 28 fourth-grade students of SDN 6 Jepon. Data were collected through observation and tests. The results show an improvement in writing skills. The average score increased from 75.78 to 84.82. Learning mastery reached 92.89% and exceeded the target of 90%. Student participation also increased to 90%. The findings indicate that PjBL creates active and meaningful learning. Students are able to develop ideas, arrange sentences, and apply language rules better through project activities.